2013
DOI: 10.1371/journal.pone.0083731
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacteriosis in Urban versus Rural Areas: A Case-Case Study Integrated with Molecular Typing to Validate Risk Factors and to Attribute Sources of Infection

Abstract: Campylobacter infection is a leading cause of bacterial gastroenteritis worldwide, and most clinical cases appear as isolated, sporadic infections for which the source is rarely apparent. From July 2005 to December 2007 we conducted a prospective case-case study of sporadic, domestically-acquired Campylobacter enteritis in rural versus urban areas and a prevalence study of Campylobacter in animal and environmental sources in the Eastern Townships, Quebec. Isolates were typed using Multilocus Sequence Typing (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
84
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(99 citation statements)
references
References 64 publications
11
84
4
Order By: Relevance
“…Consistent with previous studies (26)(27)(28)(29), our MLST analysis indicated that chickens were an important source of C. jejuni for both humans and domestic animals; this animal species commonly shared the same STs with other species (2 STs in 2 isolates from humans and 5 STs from 7 isolates of domestic animals) (Table 2 and Fig. 1).…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous studies (26)(27)(28)(29), our MLST analysis indicated that chickens were an important source of C. jejuni for both humans and domestic animals; this animal species commonly shared the same STs with other species (2 STs in 2 isolates from humans and 5 STs from 7 isolates of domestic animals) (Table 2 and Fig. 1).…”
Section: Discussionsupporting
confidence: 90%
“…Data from Canada also support the finding that broiler chickens are a major source of Campylobacter species. There are, however, indications that chicken-associated Campylobacter infections may be more common in urban dwellers than in rural dwellers (326,327). One study reported the levels of thermotolerant Campylobacter species to be three times higher in organic broilers than in conventional broilers (54.2% versus 19.7%) (328), suggesting that the likelihood of purchasing Campylobacter-contaminated broiler meat is higher for organic sources than for conventional sources.…”
Section: Poultrymentioning
confidence: 99%
“…The seasonal peak is probably associated with summer activities, including increased outdoor exposures like contacts with animals and soil, barbecuing, consumption of water from private wells, and swimming in natural waters (4,5). On the whole, poultry and poultry products have been shown to be a major source of C. jejuni infections in humans (6)(7)(8)(9).…”
mentioning
confidence: 99%
“…In this study, Campylobacter isolates were collected from domestically acquired infections in three midsized districts located outside the metropolitan area. Earlier studies have shown that risk factors and incidences of Campylobacter infections may vary in different geographical areas (6,13).…”
mentioning
confidence: 99%